25. EPIDEMIOLOGY AND SOME CHARACTERISTICS OF DENGUE HEMORRHAGIC FEVER IN CA MAU PROVINCE PERIOD 2020-2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the epidemiological characteristics and certain factors related to the classification of Dengue hemorrhagic fever severity, such as place of residence, age group, gender, access to medical facilities after detection, overweight - obesity in Ca Mau province period 2020-2024.Methods: Data were retrieved from the Ministry of Health’s infectious disease management software; 6382 children met the criteria for analyzing the incidence rate, grading, and determining the relationship through logistic regression.Results: Males had a higher incidence of measles (57.54% vs. 42.46%), rural children accounted for 70.87% compared to 29.13% in urban areas. The 6-15 age group accounted for 52.1% of cases; 53.02% went to medical facilities after ≥ 3 days. Regarding the classification of Dengue hemorrhagic fever warning, severe, rural patients had a higher rate (6.04% vs. 5.16%, OR = 1.44), overweight-obesity (11.89% vs. 5.05%, ORMH = 3.49). The rate of warning - severe Dengue hemorrhagic fever was high in children under 1 year old (14.91%) while there was no difference in other age groups. Late hospitalization increased the risk of severe classification (ORMH = 2.36). The number of cases started to increase from May and peaked in August.Conclusion: Factors such as place of residence, young age group, hospitalization time, and overweight - obesity status are clearly related to the incidence and classification of Dengue hemorrhagic fever. The study emphasizes the need to strengthen and improve access to health services, especially in rural areas, to effectively control Dengue hemorrhagic fever, especially during the rainy months.
Keywords: Dengue hemorrhagic fever; classification; age group